2014
DOI: 10.1038/leu.2014.233
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping the HLA ligandome landscape of acute myeloid leukemia: a targeted approach toward peptide-based immunotherapy

Abstract: Identification of physiologically relevant peptide vaccine targets calls for the direct analysis of the entirety of naturally presented human leukocyte antigen (HLA) ligands, termed the HLA ligandome. In this study, we implemented this direct approach using immunoprecipitation and mass spectrometry to define acute myeloid leukemia (AML)-associated peptide vaccine targets. Mapping the HLA class I ligandomes of 15 AML patients and 35 healthy controls, more than 25 000 different naturally presented HLA ligands we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
136
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(142 citation statements)
references
References 55 publications
(63 reference statements)
6
136
0
Order By: Relevance
“…[9][10][11] However, analyzing the antigenome of hematologic malignancies, we have recently demonstrated that nonmutated antigens are relevant targets of spontaneous antileukemia T-cell responses. 12,13 The strategy implemented in these studies differentially maps the naturally presented HLA ligandomes of hematologic cells in health and disease by mass spectrometry and was found to efficiently identify relevant tumorassociated antigens (TAAs).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, analyzing the antigenome of hematologic malignancies, we have recently demonstrated that nonmutated antigens are relevant targets of spontaneous antileukemia T-cell responses. 12,13 The strategy implemented in these studies differentially maps the naturally presented HLA ligandomes of hematologic cells in health and disease by mass spectrometry and was found to efficiently identify relevant tumorassociated antigens (TAAs).…”
Section: Introductionmentioning
confidence: 99%
“…However, considering the relatively low number of MHC-peptide complexes per cell and the potential MS detection limits, the majority of the data on self-, cancer, or pathogen MHC peptidomes come from immortalized cell lines (5)(6)(7)(8) or from models using cell lines engineered to secrete soluble MHC-bound peptide complexes (9)(10)(11), as both systems allow growth of high numbers of cells for peptide isolation. The improvements in peptide isolation and MS-based approaches led to the discovery of numerous MHC-I ligands presented by B cells or by patients' tumors (12)(13)(14) and the identification of virusderived MHC-bound peptides, including vaccinia virus and HIV presented by surface or soluble HLA (5,9,(15)(16)(17). These approaches identified self-and virus-derived noncanonical peptides and demonstrated that direct identification of peptides from infected cells will define the immunopeptidome relevant for the design of HIV immunogens.…”
mentioning
confidence: 99%
“…Determining the absolute number of cell surface MHC molecules by flow cytometry and/or mass spectrometry is therefore an important initial step when establishing a new model system (28,29). On average, we noted from pertinent literature reports that the usage of at least ϳ5 ϫ 10 8 cells expressing ϳ2 ϫ 10 5 MHC molecules per cell was a minimum requirement for the exploration of cellular immunopeptidomes (3,4). Cell lines expressing low levels of endogenous class I molecules (e.g.…”
mentioning
confidence: 99%
“…We also highlight selected biological applications and discuss important current technical limitations that need to be solved to accelerate the development of this field. The immunopeptidome is referred to as the collection of peptides associated with and presented by major histocompatibility complex (MHC) molecules (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). MHC-associated peptides are recognized by T lymphocytes that are in turn activated to eliminate abnormal cells such as pathogen-infected and cancer cells.…”
mentioning
confidence: 99%